Investigating the increase in the specialized performance of athletes using artificial neural network (ANN) exercises - Ma, Shuzhen (Nature Research, 2025)
Badminton, a dynamic and fast-paced racket sport, demands a unique combination of physical, technical, and cognitive abilities from its players. This study investigates the impact of a tailored core strength training program on the specialized performance of elite badminton athletes, with the aim of unlocking their full potential and improving overall well-being. The research involved a cohort of national-level badminton players who underwent a 12-week core strength training intervention. The program was designed using principles of progressive overload and targeted the development of core stability, power, and explosiveness—essential attributes for high-level badminton performance. Throughout the study, the athletes’ progress was evaluated through a comprehensive assessment battery, including measures of shot velocity, agility, jump height, and sport-specific technical proficiency. Additionally, the researchers examined the impact of the training regimen on the athletes’ mental health and resilience, using validated psychological questionnaires. The results show that the core strength training program led to significant improvements in the athletes’ explosive shot power, stability, and agility—key determinants of badminton success. Notably, the intervention also had a positive effect on the participants’ mental well-being, with increased levels of self-confidence, focus, and emotional regulation reported. This study utilized an artificial neural network (ANN) to investigate the relationships between core stability, core power, and performance indicators (agility, jump height, mental well-being) to predict and optimize conditions for enhancing specialized athletic performance. The ANN model demonstrated the ability to capture complex, nonlinear relationships and provide accurate predictions. These results suggest that integrating core-focused training into the preparation of elite badminton athletes can be a crucial strategy for enhancing their specialized performance, reducing injury risk, and promoting holistic well-being. The study shows the importance of tailored, sport-specific approaches to athletic development and provides valuable insights for coaches, sports scientists, and healthcare professionals working with high-performance badminton players.